Características morfológicas do corpo lúteo de vacas Nelore (Bos taurus indicus) nos terços inicial, médio e final da gestação - Patricia Ramos Xavier (2011)
Morphological characteristics of the corpus luteum were evaluated in 48 pregnant Nelore cows slaughtered in the slaughterhouse located in the city of Araguari-MG. The ovaries with the corpus luteum were collected, identified and divided into three groups, considering the stadium of gestation and classified for the size of foetus: (Group I) eleven animals with gestation of up to 90 days, (Group 2) twenty animals with gestation between 90 and 180 days and (Group 3) 17 animals with gestation between 180 and 261 days. The corpus luteum were dissected and submitted the histological processing and evaluations under light microscopy. The frequency of the corpus luteum was higher in the right ovary. The mean nuclear diameter of the large and small luteinic cells did not alter in the three groups. The animals with gestation up to 100 days presented higher proportion of endotelial cells and pericites. The third period of gestation presented smaller proportion of cytoplasm and nucleus of steroidogenical luteal cells, higher number of the degenerated cells and an increase of the conjunctive tissue, fibroblasts and extracellular matrix percentage.